Methods And Approaches for Monitoring and Assessing Educators' Performance - Fayziyeva Mabudakhon Mukhammadjonovna (Peerian Journals Publishing, 2024)
Assessing the activities of educators is crucial for ensuring the quality of education and promoting continuous improvement in teaching practices. This scientific article explores various methods and approaches for monitoring and assessing educators' performance. It examines traditional evaluation methods, such as classroom observations and student evaluations, as well as innovative approaches, including self-reflection practices and peer evaluations. Additionally, it discusses the benefits and challenges associated with each method and highlights the importance of a comprehensive and multifaceted approach to effectively evaluate educators' effectiveness. By implementing robust monitoring and assessment strategies, educational institutions can enhance professional development, support instructional improvement, and ultimately enhance the learning experiences of students.
Keywords: educators; monitoring; assessment; teaching practices